Power transmission conductor and method for producing the same
Patent Information
- Application Number
- CN202611366039.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-04
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]本申请实施例提供一种用于电力输送导线及其制备方法,以解决或缓解上面提出的一项或更多项技术问题
[0008]本申请实施例的第二方面,在电解液中加入乙二醇和丙三醇,通过形成络合物降低离子扩散速率,以延缓酸蚀刻效应,形成更多晶体氧化铝。在阳极氧化过程中,电解液粘度增大,离子扩散速率降低,硫酸对新生氧化铝膜的化学溶解得到有效抑制,使纳米孔在生成-溶解动态平衡中以生长为主导,获得孔壁完整、孔径均匀的散热小孔结构,无需依赖后续扩孔步骤。该导线表现出较好的抗拉强度、硬度,且覆盖层和本体之间具有较好的结合力。
Smart Images

Figure CN123017626A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of electrical wire technology, and more particularly to a power transmission conductor and a method for its preparation. Background Technology
[0002] The seasonal surge in electricity consumption during summer and winter puts immense pressure on power grid infrastructure such as transmission lines and switching equipment. The power grid is struggling to meet the increasing demand, leading to a surge in transmission and distribution equipment failures. These failures primarily include those caused by grid overload, such as transformer overheating and insulation aging, circuit breaker jamming and contact erosion, line hardware breakage and galloping, as well as insulator flashover and joint overheating. However, while electrical wires have good heat dissipation capabilities, they often suffer from insufficient strength.
[0003] It should be noted that the above content is not necessarily prior art, nor is it intended to limit the scope of protection of this application. Summary of the Invention
[0004] This application provides a method for preparing a power transmission conductor and a method thereof to solve or alleviate one or more of the technical problems mentioned above.
[0005] A first aspect of this application provides a power transmission conductor. The conductor includes a body and a covering layer covering at least a portion of the surface of the body. The body is made of aluminum, and the covering layer is made of aluminum oxide. The covering layer has a porous structure, and hydroxyl groups are loaded on the pores of the covering layer and the pores. The porosity of the pores is 30%-60%.
[0006] The conductor of the first aspect of this application exhibits both good heat dissipation capability and good strength. Specifically, the alumina capping layer is configured as a porous structure with a porosity of 30%-60%. This allows the capping layer to effectively absorb and disperse strain energy through the elastic deformation of the pore walls and the closure effect of the pores when subjected to external tensile or bending stress, preventing the propagation of microcracks. The porous structure increases the actual heat dissipation surface area of the capping layer by several to tens of times compared to a dense alumina layer of the same thickness, significantly enhancing the heat exchange efficiency of the capping layer. The pores provide physical space for micro-convection of air, forming an effective heat conduction and convection combined heat dissipation path. The hydroxyl groups contribute to the formation of a high-quality capping layer and increase the hydrophobicity of the conductor.
[0007] A second aspect of this application provides a method for preparing a power transmission conductor. The method includes: anodizing an aluminum wire to obtain a conductor, the conductor comprising a body and a covering layer covering at least a portion of the surface of the body, the covering layer comprising aluminum oxide, the covering layer having a porous structure, hydroxyl groups loaded on the covering layer and the channels of the pores, and the porosity of the pores being 30% to 60%; the electrolyte for anodizing comprising sulfuric acid and additives, the additives comprising ethylene glycol and glycerol, and the volume fraction of the additives being 5% to 20% based on the total volume of the electrolyte.
[0008] In a second aspect of this application, ethylene glycol and glycerol are added to the electrolyte to form a complex, reducing the ion diffusion rate and thus delaying the acid etching effect, resulting in the formation of more crystalline alumina. During the anodic oxidation process, the electrolyte viscosity increases, the ion diffusion rate decreases, and the chemical dissolution of the newly formed alumina film by sulfuric acid is effectively suppressed. This allows the nanopores to grow primarily in the formation-dissolution dynamic equilibrium, resulting in a heat-dissipating micropore structure with intact pore walls and uniform pore size, without relying on subsequent pore-expanding steps. This conductive wire exhibits good tensile strength and hardness, and there is good adhesion between the capping layer and the bulk. Attached Figure Description
[0009] In the accompanying drawings, unless otherwise specified, the same reference numerals throughout the various drawings denote the same or similar parts or elements. These drawings are not necessarily drawn to scale. It should be understood that these drawings depict only some embodiments disclosed in this application and should not be construed as limiting the scope of this application.
[0010] Figure 1 The images show the microstructure of the wires in Examples 1-3 and Comparative Example 1.
[0011] Figure 2 These are cross-sectional images of the conductors in Comparative Example 1 and Example 2.
[0012] Figure 3 These are the voltage-time curves for anodizing in Comparative Example 1 and Example 2.
[0013] Figure 4 This is the stress-strain curve of the conductor in Example 2.
[0014] Figure 5 It is the stress-strain curve of the aluminum conductor itself.
[0015] Figure 6 The graph shows the friction coefficient results for the wires in Example 2 and Comparative Example 5.
[0016] Figure 7 The wear curves of the wires in Example 2 and Comparative Example 5 are the wear marks after 5 minutes. Detailed Implementation
[0017] The embodiments of this application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain this application, and should not be construed as limiting this application. It should be noted that, unless otherwise specified, the embodiments and features in the embodiments of this application can be combined with each other.
[0018] It should be noted that the terms "first," "second," etc., used in this application are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that such terms can be used interchangeably where appropriate so that the embodiments of this application described herein can be implemented, for example, in orders other than those illustrated or described herein. Furthermore, the terms "comprising" and "having," and any variations thereof, are intended to cover non-exclusive inclusion; for example, a process, method, system, product, or apparatus that comprises a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to such processes, methods, products, or apparatus.
[0019] In this application, when numerical intervals (i.e., numerical ranges) are involved, unless otherwise specified, the distribution of selectable numerical values within the numerical interval is considered continuous, and includes the two endpoints of the numerical interval (i.e., the minimum and maximum values), as well as every numerical value between these two endpoints. Unless otherwise specified, when a numerical interval refers only to integers within that numerical interval, it includes the two endpoint integers of the numerical range, as well as every integer between the two endpoints, which is equivalent to directly listing every integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be merged. In other words, unless otherwise specified, the numerical ranges disclosed in this application should be understood to include any and all subranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, percentage, ratio, etc. The term "numerical interval" can be broadly included to include percentage intervals, ratio intervals, proportion intervals, etc.
[0020] A first aspect of this application provides a power transmission conductor. The conductor includes a body and a covering layer covering at least a portion of the surface of the body. The body is made of aluminum, and the covering layer is made of aluminum oxide. The covering layer has a porous structure, and hydroxyl groups are loaded on the pores of the covering layer and the pores. The porosity of the pores is 30%-60%.
[0021] The conductor of the first aspect of this application exhibits both good heat dissipation capability and good strength. Specifically, the alumina capping layer is configured as a porous structure with a porosity of 30%-60%. This allows the capping layer to effectively absorb and disperse strain energy through the elastic deformation of the pore walls and the closure effect of the pores when subjected to external tensile or bending stress, preventing the propagation of microcracks. The porous structure increases the actual heat dissipation surface area of the capping layer by several to tens of times compared to a dense alumina layer of the same thickness, significantly enhancing the heat exchange efficiency of the capping layer. The pores provide physical space for micro-convection of air, forming an effective heat conduction and convection combined heat dissipation path. The hydroxyl groups contribute to the formation of a high-quality capping layer and increase the hydrophobicity of the conductor.
[0022] In some embodiments, the covering layer is an alumina film, and the average pore size of the pores on the alumina film is 30nm-40nm, such as 30nm, 33nm, 35nm, 38nm, 40nm, etc. This provides ample interfacial channels for heat transfer to the external environment, thereby improving heat exchange efficiency.
[0023] In some embodiments, in the direction of the capping layer pointing towards the body, the capping layer has a plurality of depth layers stacked sequentially, wherein the absolute value of the porosity difference between any two adjacent depth layers is ≤3%, and the difference between the maximum and minimum porosity of the plurality of depth layers is ≤5%. This pore formation is based on the addition of ethylene glycol and propylene glycol during the preparation process, resulting in a capping layer with complete and uniform pore size distribution.
[0024] Optionally, the thickness of the capping layer is 20μm-40μm, such as 20μm, 23μm, 25μm, 30μm, 33μm, 36μm, 40μm, etc. Thus, the capping layer possesses sufficient mechanical strength while avoiding stress concentration and brittle fracture problems caused by excessive thickness.
[0025] In some embodiments, the diameter D of the conductor body and the thickness H of the covering layer satisfy the ratio D / H = 60~180. This ratio ensures that the alumina layer has sufficient thickness for reliable heat dissipation while avoiding excessive thickness that could reduce the conductor's cross-sectional area and affect conductivity. Simultaneously, this thickness ratio promotes strong adhesion of the alumina layer and reduces the risk of cracking when the conductor is bent. Furthermore, this range balances the controllability and economy of the manufacturing process, facilitating production testing and cost optimization.
[0026] A second aspect of this application provides a power transmission conductor. The method includes anodizing an aluminum wire to obtain a conductor comprising a body and a covering layer covering at least a portion of the surface of the body. The covering layer comprises aluminum oxide and has a porous structure. Hydroxyl groups are loaded onto the pores of the covering layer and the pores, and the porosity of the pores is 30%-60%. The electrolyte for anodizing comprises sulfuric acid and additives, the additives comprising ethylene glycol and glycerol, wherein the volume fraction of the additives is 5%-20% based on the total volume of the electrolyte.
[0027] In a second aspect of this application, ethylene glycol and glycerol are added to the electrolyte to form a complex, reducing the ion diffusion rate and thus delaying the acid etching effect, resulting in the formation of more crystalline alumina. During the anodic oxidation process, the electrolyte viscosity increases, the ion diffusion rate decreases, and the chemical dissolution of the newly formed alumina film by sulfuric acid is effectively suppressed. This allows the nanopores to grow primarily in the formation-dissolution dynamic equilibrium, resulting in a heat-dissipating micropore structure with intact pore walls and uniform pore size, without relying on subsequent pore-expanding steps. This conductive wire exhibits good tensile strength and hardness, and there is good adhesion between the capping layer and the bulk.
[0028] Sulfuric acid in the electrolyte helps form a dense porous film structure with smaller pore size (below 80 nm), higher porosity, and better uniform load transfer, reducing stress concentration and thus improving the mechanical strength and crack resistance of the film. Phosphoric acid is not added to the electrolyte because it leads to the formation of even larger pores (above 300 nm), and the stronger acid etching effect can easily cause the pore structure to collapse, resulting in a decrease in porosity and density, ultimately leading to a significant deterioration in mechanical properties.
[0029] The additive is a mixture of ethylene glycol and glycerol, and the additive is 5% to 20%, for example, 5%, 10%, 15%, 20%, etc.
[0030] In some embodiments, before anodizing the aluminum wire, the aluminum wire can be alkali-dissolved and cleaned to remove the oxide film on the surface of the aluminum wire, thereby forming a coating layer with better film quality.
[0031] Optionally, the concentration of the alkaline solution is 0.3 mol / L to 1 mol / L, for example, 0.3 mol / L, 0.5 mol / L, 0.8 mol / L, 1.0 mol / L, etc.
[0032] Optionally, the alkali dissolution time is 10 min to 20 min, for example, 10 min, 13 min, 15 min, 18 min, 20 min, etc.
[0033] Optionally, the cleaning is performed using ethanol or water, and the cleaning process is accompanied by ultrasonic treatment for 0.5 h to 1 h.
[0034] In some specific examples, the alkali-dissolved aluminum wire is placed in clean water and then ultrasonically cleaned to remove surface residues.
[0035] In some embodiments, after anodizing the aluminum wire, the anodized product is directly subjected to phosphoric acid immersion and ultrasonic cleaning to ensure that the obtained wire has almost no residual impurities and retains a complete and uniform pore size. Optionally, the phosphoric acid immersion conditions include: a phosphoric acid concentration of 0.3 mol / L to 1.5 mol / L and an immersion time of 10 min to 30 min. Optionally, the ultrasonic cleaning time is 20 min to 40 min.
[0036] In some embodiments, the electrolyte temperature is controlled at 10~30℃ during the anodizing process, the cathode is a graphite plate or stainless steel, and the current density applied to the conductor during the anodizing process is 0.01A / cm. 2 ~3A / cm 2 The oxidation time is controlled between 5 and 40 minutes. Therefore, by controlling the current density and oxidation time during the anodizing process, as well as the hydroxyl groups introduced by ethylene glycol and glycerol, the film quality is high, and the resulting coating has good mechanical properties.
[0037] Among them, the voltage-time curve of anodizing can be divided into three stages: the voltage rises sharply first, reaches the maximum value and then drops rapidly, and finally tends to a stable value. Here, the three stages of the curve correspond to the three processes of anodizing. First, the voltage rise stage corresponds to the formation period of the dense barrier layer. When the DC current is applied to the aluminum surface, a dense oxide layer is quickly formed on the aluminum surface. Since Al2O3 has a large barrier layer resistance, the anodizing voltage rises rapidly in order to maintain the constant current mode [1]. The chemical reaction formula for the formation of the inner oxide barrier layer is as follows: Al → Al 3+ + 3e - 2Al + 3O 2- → Al2O3 + 6e - 2Al + 6OH - → Al2O3 + H2O + 6e - Secondly, the decreasing phase of the anodic oxidation voltage corresponds to the dissolution period of the anodic oxide layer. Specifically, the current density at defects in the anodic oxide layer is typically higher, leading to a more vigorous dissolution reaction. Under a uniform electric field, the induced dissolution rate results in pore formation, and the increase in current density at these pores ultimately promotes the formation of nanoporous structures.
[0038] Third, the stable voltage phase corresponds to the growth phase of the nanoporous structure evolving into a regular morphology. During this phase, the growth of the porous structure is accompanied by the formation and dissolution of the anodic oxide film. Due to the volume expansion of the nanoporous structure, there is mutual repulsive stress between adjacent nanopores. The hexagonal close-packed structure is in its most stable state, and the anodic oxide nanopores ultimately form a hexagonal array structure. The chemical reaction formula for the dissolution process is as follows: Al₂O₃ + 6H₂O → Al₂O₃ + 6H₂O + → 2Al 3+ + 3H2O.
[0039] In some embodiments, the additive introduces hydroxyl groups into the system, effectively reducing the internal stress caused by the volume expansion of the oxide film, so that the obtained porous alumina coating layer maintains sufficient hardness while possessing significantly improved flexibility and bending resistance. Optionally, in the additive, the volume ratio of ethylene glycol to glycerol is (1-3):1, for example, 1:1, 2:1, or 3:1.
[0040] In this application, the tensile strength of the conductor obtained by the preparation method is increased by at least 20%. The tensile strength is tested using a universal testing machine.
[0041] In this application, the current carrying capacity of the conductor obtained by the preparation method is increased by at least 11% at 70°C.
[0042] Exemplary embodiments according to this application will now be described in more detail with reference to the accompanying drawings. It should be understood that these exemplary embodiments may be implemented in many different forms and should not be construed as being limited to the embodiments set forth herein.
[0043] Example 1 (1) Immerse the aluminum wire in a 0.8 mol / L sodium hydroxide solution for 15 min to remove the natural oxide film on the surface; (2) Transfer the above aluminum wires into an alcohol solution or pure water and sonicate for 0.8 hours; (3) The aluminum wire is anodized. The anodizing electrolyte is a sulfuric acid solution with a concentration of 0.8 mol / L. A mixture of ethylene glycol and glycerol, accounting for 5% of the total volume of the electrolyte, is added. The volume ratio of ethylene glycol to glycerol is 1:2. The electrolyte temperature is controlled at 25°C by a chiller. A graphite plate or stainless steel sheet is used as the cathode. (4) During anodizing, the current density applied to the wire is 0.2 A / cm. 2 The oxidation time is 10 min; (5) The prepared anodic oxide wire was immersed in 1 mol / L phosphoric acid for 20 min to remove the overgrown structural debris on the surface. Then the wire was ultrasonically cleaned in pure water for 30 min.
[0044] Example 2 (1) Immerse the aluminum wire in a 0.8 mol / L sodium hydroxide solution for 15 min to remove the natural oxide film on the surface; (2) Transfer the above aluminum wires into an alcohol solution or pure water and sonicate for 0.8 hours; (3) The aluminum wire is anodized. The anodizing electrolyte is a sulfuric acid solution with a concentration of 0.8 mol / L. A mixture of ethylene glycol and glycerol, accounting for 10% of the total volume of the electrolyte, is added. The volume ratio of ethylene glycol to glycerol is 1:2. The electrolyte temperature is controlled at 25°C by a chiller. A graphite plate or stainless steel sheet is used as the cathode. (4) During anodizing, the current density applied to the wire is 0.2 A / cm. 2 The oxidation time is 10 min; (5) The prepared anodic oxide wire was immersed in 1 mol / L phosphoric acid for 20 min to remove the overgrown structural debris on the surface. Then the wire was ultrasonically cleaned in pure water for 30 min.
[0045] Example 3 (1) Immerse the aluminum wire in a 0.8 mol / L sodium hydroxide solution for 15 min to remove the natural oxide film on the surface; (2) Transfer the above aluminum wires into an alcohol solution or pure water and sonicate for 0.8 hours; (3) The aluminum wire is anodized. The anodizing electrolyte is a sulfuric acid solution with a concentration of 0.8 mol / L. A mixture of ethylene glycol and glycerol, accounting for 15% of the total volume of the electrolyte, is added. The volume ratio of ethylene glycol to glycerol is 1:2. The electrolyte temperature is controlled at 25°C by a chiller. A graphite plate or stainless steel sheet is used as the cathode. (4) During anodizing, the current density applied to the wire is 0.2 A / cm. 2 The oxidation time is 10 min; (5) The prepared anodic oxide wire was immersed in 1 mol / L phosphoric acid for 20 min to remove the overgrown structural debris on the surface. Then the wire was ultrasonically cleaned in pure water for 30 min.
[0046] Comparative Example 1 (1) Immerse the aluminum wire in a 0.8 mol / L sodium hydroxide solution for 15 min to remove the natural oxide film on the surface; (2) Transfer the above aluminum wires into an alcohol solution or pure water and sonicate for 0.8 hours; (3) The aluminum wire is anodized. The anodizing electrolyte is a sulfuric acid solution with a concentration of 0.8 mol / L. The electrolyte temperature is controlled at 25℃ by a chiller. A graphite plate or stainless steel sheet is used as the cathode. (4) During anodizing, the current density applied to the wire is 0.05 A / cm. 2 The oxidation time is 10 min; (5) The prepared anodic oxide wire was immersed in 1 mol / L phosphoric acid for 20 min to remove the overgrown structural debris on the surface. Then the wire was ultrasonically cleaned in pure water for 30 min.
[0047] Comparative Example 2 The wire was prepared in the same manner as in Comparative Example 1, except that the current density was 0.1 A / cm². 2 .
[0048] Comparative Example 3 The wire was prepared in the same manner as in Comparative Example 1, except that the current density was 0.2 A / cm². 2 .
[0049] Comparative Example 4 Aluminum conductors are used as conductors for power transmission.
[0050] Comparative Example 5 The wires were prepared in accordance with the method of Example 1, except that the acid in the electrolyte was phosphoric acid.
[0051] The wires of the above embodiments and comparative examples were measured as follows, and the results are shown in Table 1.
[0052] Tensile strength: Referring to GB / T 9286-98-1998 standard, the tensile strength of aluminum wire was tested using a computer-controlled horizontal hydraulic tensile testing machine (WLYW-1000, Shanghai Shenlian, China). The stress-strain curve and corresponding mechanical properties were obtained by fixing both ends of the aluminum wire sample (5 meters) with wedge-shaped end clamps and applying a continuously increasing uniaxial tensile load until the sample fractured. The tensile rate and temperature were set to 50 mm / min and 25℃, respectively.
[0053] Vickers hardness: The test method is based on GB / T9790-2021 standard. A micro Vickers hardness tester is used. Under a load of 0.098N~0.98N, at least 5 points are selected on the surface of the coating for testing, and the arithmetic mean is taken.
[0054] Current carrying capacity at 70℃: Place the conductor at an ambient temperature of 25℃, connect it to the current carrying capacity test circuit, and gradually apply alternating current. When the conductor temperature stabilizes at 70℃±1℃ (the change should not exceed ±1℃ within 30 minutes), record the current value at this time, which is the current carrying capacity at 70℃.
[0055] Aperture: The surface of the overburden layer was imaged at high magnification using a field emission scanning electron microscope (SEM). The apertures in the images were measured using image analysis software (such as ImageJ), and the arithmetic mean of their equivalent circle diameters was calculated.
[0056] Film-substrate adhesion: This test method is based on GB / T 9286-2021 "Paints and Varnishes Cross-cut Test". Film-substrate adhesion refers to the adhesion between the coating / oxide film and the substrate metal on which it is coated / grown.
[0057] Wear depth: The tribological properties of the prepared surface were tested using an Rtec MFT-5000 high-integration multi-functional tribological testing machine. The test employed a reciprocating module, using 9.5 mm diameter GCr15 steel balls as the friction pair, with a frequency of 2 Hz and a load of 1 N, for 5 minutes each time. The coefficient of friction was monitored in real time during the wear process, and the wear depth was measured using a laser confocal microscope after the experiment.
[0058] Heat dissipation performance (current carrying capacity): The test setup, conforming to DL / T 1948-2018 and T / CEC 632-2022 standards, consists of a current booster and a control platform. The control platform utilizes the BIZ-35 intelligent monitoring system for switchgear manufactured by Shanghai Sicheng Electric Equipment Co., Ltd., with an output current range of 0 to 1.5 kA. The temperature acquisition device is a TP1608 temperature monitoring instrument. In the experiment, both ends of a 3-meter test lead were connected to the output terminals of the current booster transformer, and the current magnitude was set via the control console. Multiple thermocouples were installed at different locations on the lead surface. These thermocouples were connected to the multi-channel temperature monitoring instrument for data acquisition. After each step increase in current, the temperature was recorded after the line temperature stabilized (without significant fluctuations within 60 minutes). The average value of the three thermocouple readings was taken as the representative temperature for that measurement. Based on this procedure, temperature rise curves under different current carrying capacities can be obtained, and the heat dissipation performance and actual current carrying capacity at 70℃ can be determined.
[0059] Average pore size and film thickness: The microstructure and interface features of the samples were observed using a scanning electron microscope (SEM, Zeiss Auriga, Germany), and the average pore size and film thickness were calculated and statistically analyzed using ImageJ software.
[0060] Table 1
[0061] As can be seen from the table above, Examples 1-3, using sulfuric acid / organic additives, showed that this approach could increase the tensile strength (43.2 kN) of the blank aluminum conductor (Comparative Example 4) by 0.7% to 1.4%, and particularly significantly increase the Vickers hardness (375.3 HV) of the blank aluminum conductor (Comparative Example 4) by 78.6% to 91.7%. In addition to mechanical properties, the heat dissipation performance of Examples 1-3 was improved by 6.6% to 13.0% compared to the blank aluminum conductor (Comparative Example 4) in terms of current carrying capacity (30.1 A).
[0062] Compared to the blank aluminum conductor (Comparative Examples 1-3) with sulfuric acid, Comparative Examples 4 showed a slight decrease in tensile strength (1.0%-1.6%), an increase in Vickers hardness (62.7%-75.9%), and an improvement in heat dissipation performance (5.0%-11.0%). However, compared to Examples 1-3 with sulfuric acid and organic additives, all mechanical properties and current dissipation performance decreased. This is mainly due to the formation of more amorphous alumina, which has poorer mechanical strength, bonding strength, and wear resistance. The larger pore size also led to a slight decrease in heat dissipation performance.
[0063] Compared to the blank aluminum wire (Comparative Example 4), Comparative Example 5, prepared by the phosphoric acid method, showed a significant decrease in tensile strength, decreasing by 19.4%. This is mainly due to the poor film density and adhesion of Comparative Example 5, which made it prone to breakage during tensile testing, leading to a decrease in tensile strength. Its Vickers hardness increased by 57.7% compared to the blank aluminum wire (Comparative Example 4), and its heat dissipation performance improved by 9.0%. Compared to Examples 1-3 prepared by the sulfuric acid / organic additive method, Comparative Example 5, prepared by the phosphoric acid method, showed significantly worse mechanical properties, mainly due to the higher acidity of phosphoric acid, its higher ion diffusion rate, and its stronger acid etching effect, resulting in poorer hardness and adhesion.
[0064] Figure 1 The figures show the microstructure of the wires in Examples 1-3 and Comparative Example 1. As can be seen, adding 5% additive improved the nanopore dissolution, but some pores still exhibited slight cracking. Adding 10% additive resulted in a more uniform pore structure with almost no pore dissolution or cracking. When the ethylene glycol / glycerol content reached 15%, the pore structure remained intact, but the pore size decreased and the pore walls thickened. This can be attributed to the higher concentration of additive reducing the pore dissolution rate and slowing down the pore wall erosion. Overall, adding 10% ethylene glycol / glycerol to the sulfuric acid electrolyte is beneficial for obtaining undissolved nanopore structures.
[0065] Figure 2The images show cross-sectional views of the wires in Comparative Example 1 and Example 2. The cracks in the film-substrate adhesion of the wires with 10% ethylene glycol / glycerol added are smaller than those in the unadded sample, indicating that the addition of ethylene glycol / glycerol contributes to the formation of a denser anodic oxide film.
[0066] Figure 3 These are the voltage-time curves for anodizing in Comparative Example 1 and Example 2. The overall trends of the two curves are similar, indicating that the addition of ethylene glycol / glycerol did not change the overall anodizing process.
[0067] The addition of 10% ethylene glycol / glycerol increased the stable anodic oxidation voltage, further indicating that the organic additive has a mitigating effect on the severe dissolution of the nanoporous structure. Therefore, the addition of ethylene glycol / glycerol is beneficial for forming a uniform nanoporous structure and a better-bonded anodic oxide film.
[0068] Figure 4 This is the stress-strain curve of the conductor in Example 2. Figure 5 It is the stress-strain curve of the aluminum conductor body. Figure 4 and Figure 5 The comparison shows that the conductor of this application has better mechanical properties.
[0069] Figure 6 The graph shows the friction coefficient results of the wires in Example 2 and Comparative Example 5. During the initial wear period from 0 s to 200 s, the surface friction coefficient of the wire in Example 2 was 0.8-0.9, while the surface friction coefficient of the wire in Comparative Example 1 was only 0.9-1.1. This indicates that the wires in this study have better wear resistance and demonstrate better film-substrate adhesion.
[0070] Figure 7 The wear track curves for the wires of Example 2 and Comparative Example 5 after 5 minutes of wear are shown. After 5 minutes of wear, the wear track depth on the surface of the wire in Example 2 was 4.6 μm, while the wear track depth on the surface of the wire in Comparative Example 1 increased to 7.3 μm. The wear in this study was reduced by 37.0%, showing better wear resistance.
[0071] It should also be noted that the terms "some embodiments," "other embodiments," and "embodiments" used in this application refer to specific features, structures, or characteristics described in connection with those embodiments, which are included in at least one embodiment described in the general description of this application. The appearance of the same expression in multiple places in the specification does not necessarily refer to the same embodiment. Furthermore, when a specific feature, structure, or characteristic is described in connection with any embodiment, the intention is to suggest that implementing such a feature, structure, or characteristic in conjunction with other embodiments also falls within the scope of this application.
[0072] In the above embodiments, the descriptions of each embodiment have different focuses. For parts not described in detail in a certain embodiment, please refer to the relevant descriptions in other embodiments.
[0073] It should also be noted that the above are merely preferred embodiments of this application and do not limit the scope of protection of this application. Any equivalent structural or procedural transformations made using the content of this application specification, or direct or indirect applications in other related technical fields, are similarly included within the scope of protection of this application.
Claims
1. A power transmission conductor, characterized in that, The device includes a body and a covering layer that covers at least a portion of the surface of the body. The body comprises aluminum, and the covering layer comprises aluminum oxide. The covering layer has a porous structure. The capping layer and the pore channels are loaded with hydroxyl groups; The porosity of the pores is 30%-60%.
2. The power transmission conductor according to claim 1, characterized in that, The average pore diameter is 30nm-40nm; The thickness of the covering layer is 20μm-40μm.
3. The power transmission conductor according to claim 1, characterized in that, In the direction from the cover layer to the body, the cover layer has a plurality of depth layers stacked sequentially, the absolute value of the porosity difference between any two adjacent depth layers is ≤3%, and the difference between the maximum and minimum porosity of the plurality of depth layers is ≤5%.
4. A method for preparing power transmission conductors, characterized in that, include: Anodizing an aluminum wire yields a conductor comprising a body and a covering layer covering at least a portion of the surface of the body. The covering layer comprises aluminum oxide and has a porous structure. Hydroxyl groups are loaded onto the covering layer and the channels of the pores, and the porosity of the pores is 30% to 60%. The electrolyte for anodic oxidation includes sulfuric acid and additives, the additives including ethylene glycol and glycerol, and the volume fraction of the additives is 5% to 20% based on the total volume of the electrolyte.
5. The preparation method according to claim 4, characterized in that, Prior to anodizing the aluminum wire, the process also includes: The aluminum wire was dissolved and cleaned using an alkaline solution.
6. The preparation method according to claim 5, characterized in that, The concentration of the alkaline solution is 0.3 mol / L to 1 mol / L. The alkali dissolution time is 10 min to 20 min; The cleaning is performed using ethanol or water, and the cleaning process is accompanied by ultrasonic treatment for 0.5 h to 1 h.
7. The preparation method according to claim 4, characterized in that, After the anodizing process but before obtaining the wire, the process further includes: The anodized product was sequentially subjected to phosphoric acid immersion and ultrasonic cleaning. The conditions for phosphoric acid soaking include: a phosphoric acid concentration of 0.3 mol / L to 1.5 mol / L and a soaking time of 10 min to 30 min.
8. The preparation method according to claim 4, characterized in that, The current density for the anodizing process is 0.01 A / cm². 2 ~3A / cm 2 The oxidation time is 5 min to 40 min.
9. The preparation method according to claim 4, characterized in that, In the additive, the volume ratio of ethylene glycol to glycerol is (1-3):
1.
10. The preparation method according to any one of claims 4-9, characterized in that, The tensile strength of the conductor is at least 20%; The current carrying capacity increases by at least 11% at 70°C.
